2015
DOI: 10.1016/j.jmb.2015.08.009
|View full text |Cite
|
Sign up to set email alerts
|

α-Lactalbumin:Oleic Acid Complex Spontaneously Delivers Oleic Acid to Artificial and Erythrocyte Membranes

Abstract: Human α-lactalbumin made lethal to tumor cells (HAMLET) is a tumoricidal complex consisting of human α-lactalbumin and multiple oleic acids (OAs). OA has been shown to play a key role in the activity of HAMLET and its related complexes, generally known as protein-fatty acid (PFA) complexes. In contrast to what is known about the fate of the protein component of such complexes, information about what happens to OA during their action is still lacking. We monitored the membrane, OA and protein components of bovi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
10
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 39 publications
2
10
0
Order By: Relevance
“…The α-LA component of the cytotoxic complexes confers specificity for tumor cell membranes through protein interactions that are maintained even in the lipid complex, in the presence of oleic acid [ 313 ]. Wen et al monitored the membrane, oleic acid, and protein components of bovine α-LA complexed with oleic acid (BLAOA; a HAMLET-like complex prepared at alkaline pH [ 17 ]) and how they associate with each other [ 314 ]. Using ultracentrifugation, they found that the oleic acid and lipid components follow each other closely.…”
Section: Anti-tumorigenic Activities Of α-Lactalbuminmentioning
confidence: 99%
“…The α-LA component of the cytotoxic complexes confers specificity for tumor cell membranes through protein interactions that are maintained even in the lipid complex, in the presence of oleic acid [ 313 ]. Wen et al monitored the membrane, oleic acid, and protein components of bovine α-LA complexed with oleic acid (BLAOA; a HAMLET-like complex prepared at alkaline pH [ 17 ]) and how they associate with each other [ 314 ]. Using ultracentrifugation, they found that the oleic acid and lipid components follow each other closely.…”
Section: Anti-tumorigenic Activities Of α-Lactalbuminmentioning
confidence: 99%
“…It may be that the unusual membrane effects exerted by this compound's display could explain its broad efficacy, as both lowering the membrane CSA and inducing isotropic or inverse phase components would be detrimental to cell membrane integrity. Indeed, there are many studies that link cytotoxicity or drug action to such mechanisms, including the alkylphosplipids [5], protein-fatty acid complexes delivering cytotoxic oleic acid to the membrane [54,55], and numerous membrane-active proteins and peptides [31,33,52,56]. Environmental toxicity of pollutants has also been ascribed to membrane effects in some cases [41].…”
Section: Discussionmentioning
confidence: 99%
“…These results indicate that BAMLET treatment leads to a decrease in cancer cell energy production capacity and metabolic activities. Multiple lines of investigation by others indicate that the cellular target of BAMLET is the plasma membrane [ 30 , 43 , 59 65 ]. Our bioinformatics analysis of bacterial membrane proteins revealed ATP synthase as the only membrane protein to have a structural difference in HAMLET-sensitive bacteria compared to HAMLET-resistant bacteria, the difference being the lack of subunit I in sensitive bacteria.…”
Section: Discussionmentioning
confidence: 99%
“…The many proposed cellular targets include membrane ion channels [ 29 , 47 50 ], histones [ 51 53 ], mitochondria [ 54 56 ], proteasomes [ 19 ], α-actinin [ 57 ], annexin [ 30 ], and ATP synthase [ 58 ]. Multiple lines of evidence indicate that the initial BAMLET target is the cellular membrane of cancer cells [ 30 , 43 , 59 65 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation